Pengaruh Kebijakan Promosi dan Harga Tiket Masuk Terhadap Keputusan Wisatawan Berkunjung di Objek Wisata Candi Gedong Songo Kabupaten Semarang - Sugiyanto Sugiyanto; Agustin Tri Hastuti; Inggris Yossi Pranatika; Siti Amri Alimatul Muflikhah; Mohammad Syafrizal Affandi (Public Service and Governance Journal, 2025)
Gedong Songo Temple is a Hindu cultural relic from the Sanjaya Dynasty era which was discovered in 1804 and is located at an altitude of 1,220 to 1,310 meters above sea level. The Minister of Education and Culture designated Gedong Songo Temple as a National Ranked Cultural Heritage Area in 2015 whose preservation must be maintained, including preserving the natural beauty around the Gedong Songo Temple area. This research is to explain  the influence of promotional policies and entrance ticket prices on tourists' decisions to visit the Gedong Songo Temple tourist attraction in Semarang Regency. This type of explanatory research The population in the research was all people who visited the Gedong Songo tourist attraction, Semarang Regency using non-random sampling techniques using incidental sampling and data collection techniques using question nairesvia Google Forms. Meanwhile, hypothesis testing uses statistical The results of the research are (1) The promotion policies with a score of 65.65% and X1Y correlation coefficient show a value of 0.658, indicating a positive coefficient direction. (2) The ticket price enters with a score of 77.77%% and the results of the X2Y correlation coefficient showa value of 0.660, indicating a positive coefficient direction. (3) The hypothesis states that there is an influence of promotional policies and entrance ticket prices on the decision to visit the Gedong Songo Temple tourist attraction, is "accepted". The suggestions in this research are 1) the Semarang Regency Government should promote the Gedong SongoTemple tourist attraction more frequently,2) theSemarang Regency Government needs to improve the existing facilities at the Gedong Songo Temple.